LIFE STYLE AND CARDIOVASCULAR APTITUDE . (Fiep Bulletin - online, 2014)
This study aimed to compare differences in cardiovascular aptitude in students of the 8th grade enrolled only in physical education classes and students that besides enrolled in physical education classes are also enrolled in sport school. This study was descriptive exploratory been evaluated 13 females and 7 males aging 13 and 14 years of a private school of Santa Cruz do Sul, RS, Brazil. The study variable was the cardiovascular aptitude obtained by a survey questionnaire and the test of 9 minutes proposed by the PROESP-BR (2000). Results showed there was not difference in the cardiovascular aptitude between the participating students that only enrolled in physical education classes plus sport clubs. It was also observed that most students did not obtain satisfactory when compared to the gold standards of health given the age and sex of the individual. Therefore, results pointed out the either physical education classes a and sport clubs have not been enough for the development of the cardiovascular aptitude of the students, i.e. they are not offering motor activities able to develop levels of fitness related to health adequate to this age interval.
Keywords: cardiovascular aptitude; physical education; school sports clubs.